2023
DOI: 10.1002/adhm.202300779
|View full text |Cite
|
Sign up to set email alerts
|

Reactive Oxygen Species‐Scavenging Nanosystems in the Treatment of Diabetic Wounds

Abstract: Diabetic wounds are characterized by drug‐resistant bacterial infections, biofilm formation, impaired angiogenesis and perfusion, and oxidative damage to the microenvironment. Given their complex nature, diabetic wounds remain a major challenge in clinical practice. Reactive oxygen species (ROS), which have been shown to trigger hyperinflammation and excessive cellular apoptosis, play a pivotal role in the pathogenesis of diabetic wounds. ROS‐scavenging nanosystems have recently emerged as smart and multifunct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 65 publications
(19 citation statements)
references
References 137 publications
1
18
0
Order By: Relevance
“…In multifunctional wound dressings, continuous release of exosomes can improve ROS damage, induce angiogenesis, enhance proliferation, granulation tissue formation, and collagen accumulation in diabetic wounds. [ 53 ] Here, in vitro experiments confirmed the promoting effect of ADSC‐exos on cell proliferation and migration. In vivo experiments showed that the scaffold based on ADSC‐exos could increase the number of blood vessels during wound repair, promote the proliferation of wound repair cells, and accelerate the healing process, which confirmed the considerable advantages of ADSC‐exos in vascularization and healing.…”
Section: Discussionsupporting
confidence: 58%
“…In multifunctional wound dressings, continuous release of exosomes can improve ROS damage, induce angiogenesis, enhance proliferation, granulation tissue formation, and collagen accumulation in diabetic wounds. [ 53 ] Here, in vitro experiments confirmed the promoting effect of ADSC‐exos on cell proliferation and migration. In vivo experiments showed that the scaffold based on ADSC‐exos could increase the number of blood vessels during wound repair, promote the proliferation of wound repair cells, and accelerate the healing process, which confirmed the considerable advantages of ADSC‐exos in vascularization and healing.…”
Section: Discussionsupporting
confidence: 58%
“…The accumulated ROS in diabetic wounds surpasses the tissue's antioxidant capacity, which remarkably retards the self-healing of wounds. 28,29 L(+)-ascorbic acid, widely recognized for its antioxidant properties and excellent biocompatibility, has been extensively applied in clinical practice, including wound healing. 22,30 To validate whether hydrogel@lipo could promote diabetic wound healing, the ROS-scavenging efficacy was tested using 2 0 ,7 0 -dichlorodihydrofluorescein diacetate (DCFH-DA) and DPPH assays.…”
Section: Antioxidant Capacity Of Hydrogel@lipomentioning
confidence: 99%
“…The surface of healthy skin is generally weakly acidic, pH = 4.2–5.9. After skin being injured, the skin will first become briefly acidic due to the production of organic acids and increased local partial pressure of carbon dioxide, and then the value of pH will increase to 7.14–8.9 owing to the leakage from the microvessels. , With the recovery of the wound, the pH value will slowly return to the normal skin level, while the chronic wound will remain alkaline because of the continuous abnormal inflammation. According to the acid–alkaline characteristics of wounds, wound dressings with different release characteristics at different wound healing stages can be designed.…”
Section: Introductionmentioning
confidence: 99%